2015
DOI: 10.1186/s13006-015-0042-9
|View full text |Cite
|
Sign up to set email alerts
|

Existential security is a necessary condition for continued breastfeeding despite severe initial difficulties: a lifeworld hermeneutical study

Abstract: BackgroundThe majority of new mothers in Sweden initiate breastfeeding and many experience initial difficulties. This experience is an important cause of early breastfeeding cessation. To increase understanding, there is a need to explore the lived experiences of the decision to continue or cease breastfeeding. The aim of this study is therefore to explain and understand how this decision is influenced by the meaning of severe initial difficulties.MethodsA lifeworld hermeneutical approach was used for the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 50 publications
1
35
0
10
Order By: Relevance
“…This study added to these findings with audio-visual evidence of how the mothers ascribed their emotions to their feelings of persistent scrutiny by the healthcare team and how the feelings persisted and fluctuated in strength over hours and days. However it is interesting that Palmér et al (2015) have suggested that when mothers are able to blame others for their breastfeeding difficulties, they are more likely to continue breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…This study added to these findings with audio-visual evidence of how the mothers ascribed their emotions to their feelings of persistent scrutiny by the healthcare team and how the feelings persisted and fluctuated in strength over hours and days. However it is interesting that Palmér et al (2015) have suggested that when mothers are able to blame others for their breastfeeding difficulties, they are more likely to continue breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report that women's satisfaction with breastfeeding is closely related to the perception that their milk is enough to nurture the infant, and not for the pleasure of breastfeeding only (Heidari, Keshvari, & Kohan, ; Zahra, Monireh, Easa, & Susan, ). Thus, when realizing that the infant was satisfied with the amount of milk offered, a woman tends to feel satisfied, regardless of whether the breastfeeding process caused her pleasure or pain (Palmér, Carlsson, Brunt, & Nyström, ).…”
Section: Discussionmentioning
confidence: 99%
“…Operational definition: Upon inspection or palpation, observe whether the breasts contain milk before the baby is positioned to start sucking (27,(45)(46)53,55,57,59,74) . before and during breastfeeding (21,(28)(29)33,49,60,63,65) . in the oropharynx (38)(39)(44)(45)52,61,65,68,(70)(71) .…”
Section: Breast Fullness Prior To Feeding (100103) -mentioning
confidence: 99%
“…Operational definition: Observe, when talking to the mother, if she is knowledgeable about techniques that help prevent nipple sensitivity (21,36,44,46,53,55,59,63,70,(73)(74)(75).…”
Section: Techniques To Prevent Nipple Tenderness (100121)mentioning
confidence: 99%